Enzymatic synthesis of triacylglycerols of docosahexaenoic acid: Transesterification of its ethyl esters with glycerol - Moreno-Pérez, Sonia; Luna, Pilar; Señoráns, Francisco J.; Guisán, José Manuel; Fernández-Lorente, Gloria (Food Chemistry, 2015)
The synthesis of docosahexaenoyl triacylglycerides at low temperature (e.g., 50°C) using biocatalysts of 6 commercial lipases adsorbed on hydrophobic supports was studied. In general, the triacylglyceride yields were very low with the exceptions of those produced with the enzymes from Candida antarctica fraction B, CALB (82%), and those produced with the enzyme from Pseudomonas fluorescens, PFL (57%). The reactions were performed under vacuum to remove the released ethanol. The yields varied widely when different derivatives of CALB were used, and they were higher when CALB adsorbed on hydrophobic supports was used (82%). One interesting by-product (18% of sn-2 monoacylglyceride of DHA) remained at the end of the synthetic process. CALB adsorbed on Sepabeads exhibited better activity and stability than did the commercial derivative Novozym 435. The best CALB biocatalyst preserved 90% of the activity after 30 days under the reaction conditions. Peer Reviewed